DIFFERENCE OF ANATOMY INFORMATION MRI KNEE JOINT ON VARIATION OF TIME REPETITION SEQUENCES STIR IN SAGITTAL SLICES - Indrati, Rini; Widyastuti, Lydia Purna; Sari, Tri Puspita; Sudiyono, Sudiyono (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Time Repetition (TR) is one of the main parameters of Inversion Recovery. Purpose: The purpose of this study to determine differences in anatomical MRI information on the variation of the knee joint TR sequences STIR Sagittal slices. Method: Type of research is experimental. The study was conducted with MRI 1.5 Tesla. Data in the form of 42 image sequences STIR MRI knee joint with TR 3500, 4000, 4500, 5000, 5500, 6000, and 6500 ms. Anatomical assessments on the anterior cruciate ligament, posterior cruciate ligament, articular cartilage, and meniscus were performed by a radiologist. Data analyzed by Friedman and Wilcoxon test. Result: The results showed that there were differences in the MRI anatomical information of the knee joint of the STIR sagitas slice in the TR variation with p-value < 0.001. There is a difference in anatomical information between TR 5000 and 6000 ms (p-value = 0.034), TR 5000 and 6500 ms (p-value = 0.024), TR 5500 and 6500 ms (p-value = 0.038). There is no difference in anatomical information between TR 4500 and 5000 ms (p-value = 0.395), TR 4500 and 5500 ms (p-value = 0.131), TR 4500 and 6000 ms (p-value = 0.078), TR 4500 and 6500 ms (p-value = 0.066), TR 5000 and 5500 ms (p-value = 0.414), TR 5500 and 6000 ms (p-value = 0.102), TR 6000 and 6500 ms (p-value = 0.083). Conclusion: The optimal value to produce anatomical information of the knee joint sagittal MRI sequences STIR is TR 4500 ms.